Study Of Wildlife Trade Protected By Social Media and Law Enforcement Efforts: Case Study At The Center For Safety and Environment Law Enforcement and Forestry In The Sulawesi Region Section III Manado - Panggalo, Andi T.; Langi, Martina Agustina; Kiroh, Hengki Johanis (Sam Ratulangi University, 2024)
The illicit wildlife trade is a significant global issue, compounded by the increasing use of social media platforms. This study explores the dynamics of protected wildlife trade through social media and evaluates law enforcement responses in North Sulawesi, Indonesia. This case study was conducted at the Regional Environmental and Forestry Law Enforcement Office in Manado, integrating interviews, surveys, and thematic analysis over a span from 2016 to 2023. Results showed that social media, particularly Facebook, was utilized in 71% of the wildlife trade cases, predominantly involving avian species. Traders employed sophisticated methods including the use of anonymous accounts and disguised packages to evade detection. Law enforcement operations have included forest security traps and wildlife circulation interventions, but challenges remain in prosecuting major financiers and dismantling international networks. It can be concluded that effective enforcement is hindered by technologically sophisticated traders and the need for more robust international cooperation and legal frameworks. Keywords: wildlife trade, social media, law enforcement, North Sulawesi. Abstrak Perdagangan satwa liar ilegal merupakan masalah global yang signifikan, yang diperparah dengan penggunaan platform media sosial yang meningkat. Studi ini mengeksplorasi dinamika perdagangan satwa liar yang dilindungi melalui media sosial dan mengevaluasi respons penegakan hukum di Sulawesi Utara, Indonesia. Studi kasus ini dilakukan di Kantor Penegakan Hukum Lingkungan dan Kehutanan Daerah di Manado, mengintegrasikan wawancara, survei, dan analisis tematik selama rentang waktu dari tahun 2016 hingga 2023. Hasil menunjukkan bahwa media sosial, khususnya Facebook, digunakan dalam 71% kasus perdagangan satwa liar, terutama melibatkan spesies burung. Para pedagang menggunakan metode yang canggih termasuk penggunaan akun anonim dan paket yang menyamar untuk menghindari deteksi. Operasi penegakan hukum telah mencakup perangkap keamanan hutan dan intervensi sirkulasi satwa liar, namun masih ada tantangan dalam menuntut para pemodal besar dan membongkar jaringan internasional. Dapat disimpulkan bahwa penegakan hukum yang efektif terhambat oleh pedagang yang cakap teknologi dan kebutuhan akan kerja sama internasional serta kerangka hukum yang lebih kuat. Kata Kunci : perdagangan satwa liar, media sosial, penegakan hukum,Sulawesi Utara.